2002
DOI: 10.1021/jp0135095
|View full text |Cite
|
Sign up to set email alerts
|

An IR Study of Hydrogen Bonding in Liquid and Supercritical Alcohols

Abstract: IR spectra in the region of the OH stretching band of liquid-like and supercritical methanol (T c = 239.4 °C, Pc = 80.8 bar), ethanol (240.9 °C, 61.4 bar), 2-propanol (235.2 °C, 47.6 bar), and 1-butanol (289.9 °C, 44.1 bar) (data from ref , J. Chem. Eng. Data 1995, 40, 1025) have been recorded over a wide range of temperature and pressure up to 450 °C and 1000 bar. The spectra were obtained using a high-pressure, high-temperature IR cell and a specially developed measuring technique, in which the integrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 71 publications
(101 reference statements)
5
53
0
Order By: Relevance
“…Therefore, fundamental studies mainly devoted to lower alcohols such as methanol and ethanol have been performed to elucidate the structure and dynamics of pure alcohols in the supercritical state. Molecular dynamics simulations, 2 NMR experiments, 3,4 neutron diffraction, 5 and vibrational spectroscopies ͑Raman 6 and infrared [7][8][9] ͒ came to the converging conclusion that hydrogen bonding still exists in the supercritical domain even at high temperatures. As a matter of fact, at about 330°C and at intermediate reduced densities r = / c =2 ͑where c is the critical density͒, the degree of hydrogen bonding was found to be about 30% that existing in liquid methanol and ethanol at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fundamental studies mainly devoted to lower alcohols such as methanol and ethanol have been performed to elucidate the structure and dynamics of pure alcohols in the supercritical state. Molecular dynamics simulations, 2 NMR experiments, 3,4 neutron diffraction, 5 and vibrational spectroscopies ͑Raman 6 and infrared [7][8][9] ͒ came to the converging conclusion that hydrogen bonding still exists in the supercritical domain even at high temperatures. As a matter of fact, at about 330°C and at intermediate reduced densities r = / c =2 ͑where c is the critical density͒, the degree of hydrogen bonding was found to be about 30% that existing in liquid methanol and ethanol at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…10 This investigation has been performed in order to clarify some quantitative disagreement between the degree of hydrogen bonding obtained with molecular dynamics ͑MD͒ simulations results, 2 NMR experiments, 3 and using IR spectroscopy. [7][8][9] This point has been critically discussed and it came out that the difficulty relies in the analysis of IR and Raman spectra in terms of clusters which is particularly difficult for methanol and ethanol. 11 Besides, tert-butanol has been the subject of a number of recent studies 12 which suggested that the extent of hydrogen bonding is less dominant in the liquid phase than in lower alcohols ͑methanol, ethanol͒ because of steric and packing effects.…”
Section: Introductionmentioning
confidence: 99%
“…The non-ester component and glycerol collectively is less than 5% for both SCM and SCE. The difference in the product obtained while using SCM and SCE is still ambiguous as shown by many researches [32,41,42]. Numerous studies [23,30] have shown the suitability of SCM in biodiesel production, while studies by Madras et al [29] and Poudel and Oh [43] have presented the suitability of SCE over SCM.…”
Section: Resultsmentioning
confidence: 99%
“…scH 2 O was injected from the top at 415 • C (or lower) while temperature of the metal solution introduced from the bottom of the reactor was kept below 30 • C. In most experiments reactor temperature (R) was 385 • C, but experiments at 355 and 260 • C were also conducted. At these temperatures, decomposition of EtOH does not take place [29]. Pressure was kept at 240 bar.…”
Section: Methodsmentioning
confidence: 99%